Trypan Blue for the Assessment of Filtering Bleb Function During Cataract Surgery. Issue 3 (March 2018) - Yung, Edward S.; Moster, Marlene R.; Sanvicente, Carina; Pluta, John; Rahmatnejad, Kamran; Patel, Arjun S.; Williams, Alice; Abramowitz, Ben; Katz, L. Jay; Pro, Michael
Abstract : Purpose: Phacoemulsification has been cited as a possible cause of bleb failure in eyes with prior trabeculectomy. No method has been developed to directly evaluate the risk of bleb failure after phacoemulsification. We investigate the use of trypan blue during cataract surgery in the setting of a preexisting trabeculectomy to evaluate the functional status of the bleb and predict postoperative bleb function. Materials and Methods: In total, 14 patients contributing 1 eye each with a history of prior trabeculectomy with mitomycin C undergoing phacoemulsification with intraocular lens implantation were enrolled in this prospective, nonrandomized clinical trial. At the time of phacoemulsification, trypan blue was instilled into the anterior chamber before capsulorhexis creation. Staining of the bleb was grouped as being mild or diffuse using intraoperative photographs. These eyes were followed for 1 year postoperatively and evaluated for intraocular pressure (IOP) control. Results: The change in IOP was not significantly different between the 2 groups ( P =0.14). A trend towards greater need for IOP-lowering medications was noted ( P <0.10) in eyes with mild bleb staining. No statistically significant difference in rates of decreased bleb function was noted at 1-year follow-up after phacoemulsification. Conclusion: The intensity of bleb staining with trypan blue during phacoemulsification is not associated with changes in IOP postoperatively. A trend towards decreased need for IOP-lowering medications was noted in eyes with diffuse bleb staining at 1 year after cataract surgery.